Defining a Methylation Signature Associated With Operational Tolerance in Kidney Transplant Recipients - Rodriguez, Ramon M.; Hernández-Fuentes, María P.; Corte-Iglesias, Viviana; Saiz, María Laura; Lozano, Juan José; Cortazar, Ana R.; Mendizabal, Isabel; Suarez-Fernandez, María Luisa; Coto, Eliecer; López-Vázquez, Antonio; Díaz-Corte, Carmen; Aransay, Ana M.; et al. (Frontiers in Immunology, 2021)
Operational tolerance after kidney transplantation is defined as stable graft acceptance without the need for immunosuppression therapy. However, it is not clear which cellular and molecular pathways are driving tolerance in these patients. We performed genome-wide analysis of DNA methylation in peripheral blood mononuclear cells from kidney transplant recipients with chronic rejection and operational tolerance from the Genetic Analysis of Molecular Biomarkers of Immunological Tolerance (GAMBIT) study. Our results showed that both clinical stages diverge in 2737 genes, indicating that each one has a specific methylation signature associated with transplant outcome. We also observed that tolerance is associated with demethylation in genes involved in immune function, including B and T cell activation and Th17 differentiation, while in chronic rejection it is associated with intracellular signaling and ubiquitination pathways. Using co-expression network analysis, we selected 12 genomic regions that are specifically hypomethylated or hypermethylated in tolerant patients. Analysis of these genes in transplanted patients with low dose of steroids showed that these have a similar methylation signature to that of tolerant recipients. Overall, these results demonstrate that methylation analysis can mirror the immune status associated with transplant outcome and provides a starting point for understanding the epigenetic mechanisms associated with tolerance.